Evaluation of anesthesia informed consent in pediatric practice - An observation cohort study - Ekta Rai; Regina Yu Ying Chen; Chia S Noi; Hwan I Hee (Wolters Kluwer Medknow Publications, 2019)
Background and Aims: An informed consent requires active participation by both physicians and patients. It is the responsibility of the physician to give the complete disclosure of information in easy language for the parent to understand. An informed consent process can be a challenge especially for the anesthetists when time is a limiting factor for patient-anesthetist interaction especially in same day admission and day surgery. The aim of this study was to subjectively evaluate the understanding and recall of the informed consent by the parents. Material and Methods: The validated survey was conducted over 10 weeks and was limited to one parent per child and to the parent who was directly involved in the consent process. Results: Majority of parents rated positively for adequate disclosure of all items of information. Consent process done on day of surgery was found to be associated with lower parental rating in adequacy of disclosure of pain relief options. Seniority of anesthetists was associated with higher parental rating of adequacy of information regarding post operative plan, specific risk of child and overall consent process. Consent for minor surgeries, on day of surgery, did not significantly affect the parental performance in their recall of disclosed information but was associated with significant lower rating of adequacy of postoperative plan. Postoperative pain is among the areas for improvement especially in day surgery cases. Conclusion: Consent taken on day of surgery was found to be associated with lower parental rating. Postoperative plan for pain required improvement especially in day surgery cases.